MONETARY INFLUENCE ON INVESTMENT IN LAMPUNG PROVINCE: SHARIA ECONOMIC ANALYSIS - Anggoro Sugeng; Fajar Setiono; Ku Abdul Muhaimin Yusof (Tasharruf: Journal Economics and Business of Islam, 2022)
This study aims to determine the effect of Interest Rates, Inflation, and Exchange Rates on Investment in Lampung Province as well as Islamic economic views on Investment. The types and sources of data use a quantitative approach, with secondary data in the form of time series data from 2007-2016. Based on multiple linear regression analysis using the T-test, it was found that: Interest Rates did not affect Investment with a significant value of 0.292> 0.05, Inflation had an effect on Investment with a significant value of 0.02 <0.05, and Exchange Rates had an effect on Investment with a significant value of 0.000 <0.05. While testing using the F test shows that: Interest Rates, Inflation, and Exchange Rates have a significant effect on Investment in Lampung Province with a significant value of 0.000 <0.05. The conclusion of this study shows that interest rates have no effect on investment; because changes in monthly interest rates do not immediately get a response from the market. In Islam, investment is highly recommended to avoid unproductive assets and must comply with Islamic principles.